2006
DOI: 10.1590/s0103-863x2006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Sentimentos e percepções da equipe de saúde frente ao paciente terminal

Abstract: Resumo: O atendimento a pacientes terminais pelas equipes de saúde, comprovadamente apontado por evidências na literatura, mostra a grande dificuldade que esses profissionais têm em lidar com o tema "morte". O presente estudo objetivou compreender como as equipes de saúde definem e vivenciam o paciente terminal. Para tanto, utilizou-se uma abordagem qualitativa que empregou a pesquisa etnográfica através de observação não-participativa, além de entrevistas semi-estruturadas nas unidades de hemato-oncologia e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
28

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
0
9
0
28
Order By: Relevance
“…Ou seja, as estruturas sociais e econômicas determinam as condições de saúde da população. Estudos destacam que uma das maiores dificuldades para o profissional da saúde é a frustração de não ter conseguido salvar o paciente, ou seja, evitar a morte [28][29][30][31][32] . A dificuldade destacada aqui não é exatamente a morte em si, mas a condição de vulnerabilidade social das pessoas ou a condição que acarreta a morte ("A morte faz parte do meu processo de trabalho, é um processo da vida [...] A violência me assusta um pouco.…”
Section: Comunicação Saúde Educaçãounclassified
“…Ou seja, as estruturas sociais e econômicas determinam as condições de saúde da população. Estudos destacam que uma das maiores dificuldades para o profissional da saúde é a frustração de não ter conseguido salvar o paciente, ou seja, evitar a morte [28][29][30][31][32] . A dificuldade destacada aqui não é exatamente a morte em si, mas a condição de vulnerabilidade social das pessoas ou a condição que acarreta a morte ("A morte faz parte do meu processo de trabalho, é um processo da vida [...] A violência me assusta um pouco.…”
Section: Comunicação Saúde Educaçãounclassified
“…In the analysis of magazines, periodicals stand out in nursing [9,11,14,16,[18][19][20]22] medical [4,17] of public health [10,21], bioethics [12] and in other areas [13,15]. Table 2 shows the characterization of selected articles, according to the authors, title, journal, volume, number and year of publication.…”
Section: Characterization Of the Articlesmentioning
confidence: 99%
“…Then the discussions will be exposed. After reviewing the research, the variety of perceptions about death, reported by studies, provided the division of articles on: life stage [9-11, 15-16, 18-21]; technicist conception [4,[12][13]17]; moving to a better place [13]; freedom from suffering [14] and unexpected interruption of life [20,22].…”
Section: Perceptions Of Brazilian Health Professionals About the Compmentioning
confidence: 99%
“…It therefore represents an enemy that must be fought (Moreira & Angelo, 2008). The context of the disease, thus acquires shades of meanings of a military structure, where fi ghts and battles need to be fought (Oliveira, 2002;Quintana et al, 2006). Warlike expressions are very common in the discourses of family caregivers, "We are here, you know, fi ghting, but, as the nutritionist said, winning some, losing others, but it is part of the game" (G2, Family G).…”
Section: The Fight Against Cancer: "Some Win Others Lose"mentioning
confidence: 99%
“…Cancer is life threatening, and therefore an enemy (Moreira & Angelo, 2008), and, in addition to coping with a borderline situation between life and death in an ICU, the cancer treatment could represent a military structure, in which there is bombing with rays, chemotherapy, invading bacteria. This war can be subtle, with covertly stipulated rules and roles (Oliveira, 2002;Quintana, Kegler, Santos, & Lima, 2006).…”
mentioning
confidence: 99%